Pyrethroid Resistance in the Major Malaria Vector Anopheles funestus is Exacerbated by Overexpression and Overactivity of the P450 CYP6AA1 Across Africa. - Ibrahim, S.S.; Amvongo-Adjia, N.; Wondji, M.J.; Irving, H.; Riveron, J.M.; Wondji, C.S. (Genes, 2018)
Resistance to pyrethroids (the ingredients in bed net insecticides) in the major malaria vector Anopheles funestus is threatening recent gains in the fight against malaria. Here, we established the role of an over-expressed P450, A. funestus CYP6AA1 in insecticides resistance. Transcription profiling of CYP6AA1 across Africa using microarray and quantitative reverse transcription polymerase chain reaction (qRT-PCR) revealed that it is significantly more over-expressed in southern African populations compared to West (Benin) and East African (Uganda). Heterologous expression in Escherichia coli coupled with metabolism assays demonstrated that CYP6AA1 metabolises type I (permethrin) and type II (deltamethrin) pyrethroids, as well as bendiocarb (a carbamate). Transgenic Drosophila melanogaster flies over-expressing CYP6AA1 were significantly more resistant to pyrethroid insecticides, permethrin and deltamethrin compared with control flies not expressing the gene, validating the role of this gene in pyrethroid resistance. In silico modelling and docking simulations predicted the intermolecular receptor-ligand interactions which allow this P450 to metabolise the pyrethroids and bendiocarb. Validation of CYP6AA1 as a pyrethroid resistance gene makes it possible to monitor the spread of resistance in the field where this P450 is over-expressed. Its potential cross-resistance role makes it necessary to monitor the gene closely to inform control programs on molecular basis of multiple resistance in the field.